Desenvolvimento de protótipo de registrador portátil para phmetria esofágica prolongada e aplicativo android para auxílio ao exame - FERREIRA, Júlia Helena dos Santos (2025)
This monograph presents the development of a portable recorder prototype for prolonged esophageal pHmetry exams, using the Arduino platform and electronic prototyping materials (low cost), as well as the creation of two versions of Android operating system applications for recording and transmitting of exam data between mobile phones and the recorder prototype for pHmetry. For this, the study of available literature, consultation with an expert in the subject and comparison with commercial product were performed. Next, the Arduino programming and assembly of the prototype were done, parallel to the creation of applications prototypes in the integrated development environment Android Studio. The tests used the calibration procedure of the equipment and pH measurements on different liquid substances, while the tests of the applications were done in physical device and through emulator of Android Studio. The results show that the prototype recorder for pHmetry is indeed portable and constructed from low cost materials. Tests have shown that your performance and accuracy registering pH values is satisfactory, presenting readings very close to the measurements indicated by the commercial recorder. The average pH readings of each device were taken. The version of the Android app for the professional responsible for the exam execution successfully performs operations, such as entering patient’s personal data. In app version whose end user is the patient the records on feeding, occurrence of symptoms and position body (patient lying or standing) are completed and displayed correctly. Both versions of the application prototypes connect via bluetooth with the prototype recorder for pHmetry efficiently, the transmission of information in both directions of the track allows effectively send in real time the pH values detected by the pHmeter in both applications. Data entered into applications is successfully saved to the register, as well as the pH values. Thus, the final versions of the prototype applications also presented good results, operating as expected and meeting established requirements for the Project, which shows it is applicability as a tool to aid the exam.